Hydrogen Bonding and Water Networks in a 3-D Coordination Polymer [Ag(bpp)]2(BDC)·8H2O (bpp = 1,3-Bis(4-pyridyl)propane; BDC = Benzene-1,4-dicarboxylic acid) - Wang, Chong-Chen; Wang, Peng (Asian Journal of Chemistry, 2010)
A 3-D coordination polymer of silver, i.e., [Ag(bpp)]2(BDC)·8H2O was obtained by evaporating the mixture of an ammonical solution containing AgNO3, benzene-1,4-dicarboxylatic acid and an acetonic solution of 1,3-bis(4-pyridyl)propane at room temperature slowly for several weeks. The crystals should be protected by vaseline oil as soon as possible after taken from mother liquid because they were unstable when exposed under air. In asymmetric unit of [Ag(bpp)]2(BDC)·8H2O , the Ag ions are coordinated in bent linear geometry by two N atoms from two different 1,3-bis(4-pyridyl)propane ligands. Benzene-1,4-dicarboxylic acid is uncoordinated to any Ag ions, playing the role of charge compensation of the cationic polymer coordination chains. The rich hydrogen bond interactions were formed by the O atoms from benzene- 1,4-dicarboxylic acid ligands and the lattice water molecules, which form novel water networks. The crystal structure reveals that 3-D framework of [Ag(bpp)]2(BDC)·8H2O is built up of 1-D [Ag(bpp)]n+ n, BDC2- counter-ions and lattice water molecules.